Seven new species of the enigmatic spider genus Paratropis Simon, 1889 (Mygalomorphae, Paratropididae) from Ecuador - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2024)
Seven new species of the enigmatic spider family Paratropididae are described from Ecuador. All new species belong to the genus Paratropis: P. carcosita sp. nov. (♀), P. pukallucha sp. nov. (♂♀), P. esmeraldas sp. nov. (♂♀), P. kapak sp. nov. (♂♀), P. pasochoa sp. nov. (♀), P. arenosa sp. nov. (♀) and P. cryptica sp. nov. (♂♀). A distribution map of all newly described species is presented.